2016
DOI: 10.3109/01676830.2015.1122816
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic orbital encephalocele: Presentation and imaging

Abstract: Orbital encephalocele is a severe and sight-threatening complication of orbital roof fractures. Post-traumatic orbital encephalocele can be challenging to diagnose on CT as patients with this condition often have associated orbital and intracranial hematoma, which can be difficult to distinguish from herniated brain tissue. When there is a high index of suspicion for encephalocele, an MRI of the orbits and brain with contrast should be obtained for additional characterization. Imaging signs that should raise s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…[ 8 ] Many authors advised magnetic resonance imaging (MRI) of the orbit as the investigation of choice. [ 2 6 8 9 ] It may not be always easy to perform MRI in emergency situation. CT of the orbit with thin axial and coronal sections is very useful in the evaluation of the orbital contents.…”
Section: Discussionmentioning
confidence: 99%
“…[ 8 ] Many authors advised magnetic resonance imaging (MRI) of the orbit as the investigation of choice. [ 2 6 8 9 ] It may not be always easy to perform MRI in emergency situation. CT of the orbit with thin axial and coronal sections is very useful in the evaluation of the orbital contents.…”
Section: Discussionmentioning
confidence: 99%
“…The etiology of the meningoencephalocele was also due to a raised intracranial pressure causing the meninges and brain parenchyma to herniate through a large (3 cm by 2 cm) orbital roof defect; a finding also found by Wei et al, especially where the orbital roof defect exceeded 2 sq cm. 10 Although in our patient the intracranial pressure will have normalized by the time he presented to us, we suspect the meninges and extraconal tissue in the superior orbit were in contact with each other for long enough for them to fuse, leading to tethering and pain. With this is mind, we recommend that any repair of an orbital roof fracture should serve to prevent transmission of intracranial pressure into the orbit and introduce a barrier to separate 1 cavity from another.…”
Section: Methodsmentioning
confidence: 62%
“…15,16 Development of a meningoencephalocele through a traumatic orbital roof defect is not inevitable, but the clinical signs that raise suspicion are progressive pulsatile exophthalmos with evidence of globe or optic nerve compression, while the radiological signs on CT are an enlarging heterogeneous orbital mass with associated widening of the roof fracture segments. 10 Cayli et al suggested a fracture diastasis greater than 2 mm increases the propensity to brain herniation in the pediatric patient population, 16 and the concept of a skull base fracture growing wider as the child grows can explain why some meningoencephaloceles develop years after the initial injury. 6 Although much more unusual this phenomenon has also been described in an adult.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations